FOR FEAR OF ISLAMIC LOOKS: A REFLECTION OF DISPLACED “SELVES” WITHIN ISLAM - Idha Nurhamidah; Sugeng Purwanto (International Journal of Humanity Studies (IJHS), 2021)
The study discusses a triggering issue of those Indonesian Muslims who frequently feel uneasy to socialize with other Muslims with Arabic looks to neutralize Islamic brotherhood in the Indonesian context of unity in diversity. A survey was made available online for over three months to get public responses concerning the issue. Sixty-two responses were collected for further analysis. Findings of the study revealed that most of the respondents expressed fear of Arabic looks because of terrorism-related activities resulting in deep personal hate. Fears were also felt due to the image that such a group of Muslims has deteriorated the local cultures of Indonesian origins. Still, others expressed fears of those distinctive individual Muslims because of a frequent political demonstration staged by those types of Muslims against engineered issues caused by discrepancies in political views to terminate the President. The authors offer recommendations for those with such Islam phobia to learn more about the truth of Islam from distinguished clerics from recognized Muslim organizations or to read Islamic literature to create peace of mind amid the wrong mindset about Islam, and finally to put aside egocentrism in the spirit of unity in diversity, only to fight against radicalism.